Effect of knowledge of sulfadoxine-pyrimethamine (SP) as prophylaxis for malaria on its uptake for intermittent preventive treatment of malaria in pregnancy (IPTp): Application of inverse probability weighted regression adjustment (IPWRA) technique - Charles Natuhamya; Edson Mwebesa; Nazarius Mbona Tumwesigye (PLoS ONE, 2025)
Introduction Malaria still remains a global health issue. In response, the World Health Organisation has continuously recommended the use of Sulfadoxine-Pyrimethamine (SP) for Intermittent Preventive Treatment of Malaria in Pregnancy (IPTp) as a malaria preventive measure for the mother and fetus, which has been implemented by the Ugandan government. In collaboration with partners, the government has created awareness of using SP for IPTp (SP-IPTp) among women mainly through media. Studies have investigated the effect of a woman’s education attainment on SP-IPTp. However, the effect of knowledge of SP as prophylaxis for malaria on SP-IPTp has not been studied. Notably, education does not necessarily have an effect on knowledge of SP for malaria prevention, and knowledge of SP as prophylaxis may not result in its significant uptake for IPTp. The purpose of this study, therefore, was to ensure baseline covariate balance and determine the effect of knowledge of SP as preventive chemotherapy on its uptake for IPTp. Methods The study utilised the Ugandan Malaria Indicator Survey dataset of 2018–19. Women aged 15–49 years who indicated their uptake status of SP during their last pregnancy formed the sample of this study. The inverse Probability Weighted Regression Adjustment technique was applied to assess the study objective. Results The findings revealed a positive and significant effect of knowledge of SP as malaria prophylaxis on its uptake for IPTp (Average Treatment Effect of the Treated or ATET =  0.163; 95% CI =  0.138–0.188). Conclusion Ensuring covariate balance while applying IPWRA resulted in more precise estimates of treatment effects. Programmes and policies that create awareness of using SP as malaria prophylaxis may serve as effective interventions towards SP-IPTp in Uganda.